The Gender Application Gap: Do Men and Women Apply for the Same Jobs? - Jonas Fluchtmann; Anita Marie Glenny; Nikolaj Harmon; Jonas Maibom (Institute of Labor Economics (IZA), 2021)
Men and women tend to hold different jobs. Are these differences present already in the types of jobs men and women apply for? Using administrative data on job applications made by the universe of Danish UI recipients, we provide evidence on gender differences in applied-for jobs for the broader labor market. Across a range of job characteristics, we find large gender gaps in the share of applications going to different types of jobs even among observationally similar men and women. In a standard decomposition, gender differences in applications can explain more than 70 percent of the residual gender wage gap.
Keywords: E24; J29; J31; J71; 330; job search; wage decomposition; firm wage premium; gender earnings gap